Study of the effect of propeller change on the energy efficiency of the JBC bulk carrier ship - حاتم, وهاد (Latakia University Journal -Engineering Sciences Series, 2025)
In this work, the effect of the propeller type on the energy efficiency of the bulk carrier JBC was studied. The CFD technique was used to achieve this purpose, where the URANS (Unsteady RANS Averaged Navier Stocks Equation) equations and the k-ω SST turbulence model were used to solve the Navier-Stokes equations. The bulk carrier JBC, the MP687 and VP1304 propellers were chosen for this study, due to the availability of a large number of experimental results for this ship and propellers, which helps to verify the quality of the numerical results that will be obtained. At first, the calculations were performed on the ship alone without any appendages, then the open water test was conducted for each of the selected propellers, in order to calibrate the mesh and numerical settings. Then, the effect of changing the propeller on the energy efficiency of the ship was studied. The comparison between the numerical and experimental results helped in choosing the correct mesh and numerical settings that give results very close to reality. The results obtained confirmed that the type of the chosen propeller has a significant impact on the energy efficiency of the ship. The results showed that the MP687 propeller improves the energy efficiency by 38% compared to the VP1304 propeller at the same power provided to the propeller. This amount of improvement is very large and confirms the importance of conducting such a study in choosing the type of propeller for the ship